Primary Cutaneous Gamma-Delta T-Cell Lymphoma With Long-Term Indolent Clinical Course Initially Mimicking Lupus Erythematosus Profundus - von Dücker, Laura; Fleischer, Mariella; Stutz, Nathalie; Thieme, Markus; Witte, Mareike; Zillikens, Detlef; Sadik, Christian D.; Terheyden, Patrick (Frontiers in Oncology, 2020)
Primary Cutaneous Gamma-Delta (γδ) T-Cell Lymphoma (PCGDTCL) is a rare primary cutaneous lymphoma of aggressive nature. Only a few cases with an initially indolent course over years have been published. PCGDTCL can mimic diseases with benign behavior in their clinical and histopathological presentation, such as lupus erythematosus profundus, but also other lymphomas, for example subcutaneous panniculitis-like T-cell lymphoma. In our patient, the results of histopathological, immunofluorescence microscopy, and clinical examinations of early lesions first led to the diagnosis of lupus erythematosus profundus. Two years after this diagnosis and 6 years after the first clinical symptoms appeared, the disease progressed with erosive and ulcerating plaques and a PCGDTCL with hemophagocytic syndrome with an aggressive course was diagnosed. A distinct correlation of clinical, histopathological, immunohistochemical, and molecular-pathological examinations is needed to differentiate between the potentially malignant and benign diseases. Re-biopsies of different skin lesions in uncertain cases are strongly indicated. This case demonstrates that an indolent clinical phenotype can precede an aggressive clinical course in PCGDTCL.